2016
DOI: 10.1371/journal.pone.0163470
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Impact Evaluated from Fat Percentage in Bone Mineral Density of Male Adolescents

Abstract: ObjectiveTo analyze bone mineral density (BMD) values in adolescents and to assess obesity impact, measured through body fat #x2013;on this variable through the assessment by DEXA.MethodologyA total of 318 males adolescents (12–17 years) were evaluated considering weight, height, body mass index (BMI), bone mineral density (BMD), fat and lean mass. BMD was assessed for the arms, legs, hips, and lumbar regions, as well as for total amount. Stratification of the nutritional status was determined by body fat (%BF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…The included publications consisted of 28 cross-sectional studies and 3 longitudinal studies [15,24,25]. Eleven studies were conducted in Europe [13,17,18,[24][25][26][27][28][29][30][31], nine in Asia [11,12,15,20,21,[32][33][34][35], seven in North America [10,14,16,19,[36][37][38], three in South America [9,39,40] and one in Oceania [41]. Twenty-eight studies used DXA machines to assess bone parameters and body composition, and three studies applied peripheral QCT for the measurement.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The included publications consisted of 28 cross-sectional studies and 3 longitudinal studies [15,24,25]. Eleven studies were conducted in Europe [13,17,18,[24][25][26][27][28][29][30][31], nine in Asia [11,12,15,20,21,[32][33][34][35], seven in North America [10,14,16,19,[36][37][38], three in South America [9,39,40] and one in Oceania [41]. Twenty-eight studies used DXA machines to assess bone parameters and body composition, and three studies applied peripheral QCT for the measurement.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…Twenty-eight studies used DXA machines to assess bone parameters and body composition, and three studies applied peripheral QCT for the measurement. Fourteen studies [13,14,[16][17][18][19]29] only reported the value of the regression coefficient, nine studies [9,11,20,[30][31][32][39][40][41] only reported the value of the correlation coefficient and eight studies [25][26][27][28]33,[36][37][38] reported both. Two studies investigated the association between LM and upper limb BMD, ten investigated the association between LM and LS BMD, eight investigated the association between LM and FN BMD and thirteen investigated the association between LM and total body BMD.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to treat OSA can increase the risk of stroke and cardiovascular disease [ 8 ]. The effects of OSA are rampant, not only regarding the quality of sleep and daytime performance, but there is also a tremendous influence on the circulatory system [ 8 , 14 ]. Repeated and recurrent nightly episodes of dyspnea from airflow collapse leads to retention of carbon dioxide and low oxygenation [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Controversially, fat accumulation due to obesity is detrimental to bone mass. Research has also indicated that obesity may affect bone metabolism by any of the following effects: increasing adipocyte differentiation and fat accumulation; decreasing osteoblast differentiation and bone formation; increasing circulating and tissue proinflammatory cytokines (promoting osteoclast activity and bone resorption); upregulating proinflammatory cytokine production; and interfering with intestinal calcium absorption, thereby decreasing calcium availability for bone formation [ 1 , 3 12 ]. Less understood are the effects and mechanisms of obesity on bone fracture healing.…”
Section: Introductionmentioning
confidence: 99%